The relationship between the levels of adiponectin HMW and the metabolic syndrome component in menopausal women - Melanie Maria Magdalena Ratulangi; Anak Agung Gede Budhiarta; Wimpie Pangkahila (Fakultas Kedokteran Universitas Udayana, 2018)
Introduction: In menopausal women, there increasing evidence of adipocyte dysfunction which result in a decrease in adiponectin HMW. The decrease in adiponectin HMW causes various pathological conditions related to aging such as metabolic syndrome. Simple adiponectin HMW measurements can evaluate early insulin resistance, metabolic disorders, or vascular health. The purpose of this study was to prove the relationship between adiponectin HMW levels and metabolic syndrome components in menopausal women. Methods: In this study, 45 postmenopausal women were used who declared physically healthy, met the criteria of metabolic syndrome based on IDF (International Diabetes Federation), willing to participate in the study and willing to fill out research forms as research subjects. This research was conducted at Panti Werdha Theodora in Makassar while the examination of HMW Adiponectin, fasting blood glucose, triglycerides, and High Density Lipoprotein was carried out in Prodia Laboratory. Result: The results showed a strong correlation between adiponectin HMW and metabolic syndrome components which included waist circumference, HDL levels, triglyceride levels, systolic blood pressure, diastolic and fasting blood glucose (p <0.05). Conclusion: It can be concluded that there was a relationship between adiponectin HMW levels and the metabolic syndrome component in menopausal women. HDL and waist circumference were the most significant factors compared to other metabolic factors associated with Adiponectin HMW.